2016
DOI: 10.1186/s12992-016-0201-9
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the intersection between alcohol consumption and antiretroviral treatment: needs assessment and design of interventions for primary healthcare workers, the Western Cape, South Africa

Abstract: BackgroundAt the points where an infectious disease and risk factors for poor health intersect, while health problems may be compounded, there is also an opportunity to provide health services. Where human immunodeficiency virus (HIV) infection and alcohol consumption intersect include infection with HIV, onward transmission of HIV, impact on HIV and acquired immunodeficiency syndrome (AIDS) disease progression, and premature death. The levels of knowledge and attitudes relating to the health and treatment out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
11
0
2
Order By: Relevance
“…The results indicate alcohol (Birhanu et al, 2014 Ghebremichael et al, 2009;Glozah et al, 2015;Kalema et al, 2015;Koopman et al, 2008;Medley et al, 2014;Onya et al, 2012;Papas et al, 2012;Peltzer & Pengpid, 2012;Schneider et al, 2016;Takahashi et al, 2018Takahashi et al, , 2017Watt et al, 2016;Wechsberg et al, 2008) as the most predominantly used substance in most of the countries. The second commonly reported type of substance used in other countries is cigarette smoking (Ali et al, 2012;Birhanu et al, 2014;Embleton et al, 2013;Gravely et al, 2018;Jradi et al, 2013;Peltzer & Pengpid, 2012;Sreeramareddy et al, 2014;Takahashi et al, 2017).…”
Section: Types Of Substances Usedmentioning
confidence: 95%
See 1 more Smart Citation
“…The results indicate alcohol (Birhanu et al, 2014 Ghebremichael et al, 2009;Glozah et al, 2015;Kalema et al, 2015;Koopman et al, 2008;Medley et al, 2014;Onya et al, 2012;Papas et al, 2012;Peltzer & Pengpid, 2012;Schneider et al, 2016;Takahashi et al, 2018Takahashi et al, , 2017Watt et al, 2016;Wechsberg et al, 2008) as the most predominantly used substance in most of the countries. The second commonly reported type of substance used in other countries is cigarette smoking (Ali et al, 2012;Birhanu et al, 2014;Embleton et al, 2013;Gravely et al, 2018;Jradi et al, 2013;Peltzer & Pengpid, 2012;Sreeramareddy et al, 2014;Takahashi et al, 2017).…”
Section: Types Of Substances Usedmentioning
confidence: 95%
“…Diverse presentations were also observed with regard to study settings. For instance, out of the 12 studies in the Southern region, 10 were from South Africa (Cubbins et al, 2012;Koopman et al, 2008;Meade et al, 2015;Medley et al, 2014;Mushanyu et al, 2017;Onya et al, 2012;Peltzer & Pengpid, 2012;Scheibe et al, 2016;Schneider et al, 2016;Watt et al, 2016;Wechsberg et al, 2008), and the study settings were urban (Koopman et al, 2008;Peltzer & Pengpid, 2012;Scheibe et al, 2016;Wechsberg et al, 2008), rural (Cubbins et al, 2012), and peri-urban areas (Meade et al, 2015;Onya et al, 2012;Watt et al, 2016).…”
Section: Characteristics Of the Study Populationmentioning
confidence: 99%
“…154 . Outra informação importante é a de que o TUA acelera a progressão da AIDS, mesmo que os ARVs sejam utilizados de forma correta, afetando negativamente a absorção e o metabolismo destes medicamentos 13,155 . Em adição a isso, este transtorno aumenta o risco de DSTs e de transmissão do HIV, e nesse cenário as chamadas "superinfecções ou coinfecções" podem ocorrer aumentando a probabilidade de resistência aos tratamentos medicamentosos 156 .…”
Section: Relações Entre Tua E Terapia Com Arvsunclassified
“…While South Africa has exceptional HIV treatment expertise, there is a severe human resource shortage for specialist alcohol and other substance use disorder treatment [16]. With only 0.32 psychologists, 0.28 psychiatrists, and 0.4 social workers for every 100,000 individuals, the current workforce lacks the knowledge and skill needed to address the intertwined public health crises of alcohol and HIV [17]. A qualitative study of primary healthcare workers, nurses, and lay workers in South Africa found that health professionals treating HIV lacked basic knowledge about: the criteria for harmful alcohol use; screening tools to assess risky alcohol use; and effective interventions to treat alcohol problems [17].…”
Section: Introductionmentioning
confidence: 99%
“…With only 0.32 psychologists, 0.28 psychiatrists, and 0.4 social workers for every 100,000 individuals, the current workforce lacks the knowledge and skill needed to address the intertwined public health crises of alcohol and HIV [17]. A qualitative study of primary healthcare workers, nurses, and lay workers in South Africa found that health professionals treating HIV lacked basic knowledge about: the criteria for harmful alcohol use; screening tools to assess risky alcohol use; and effective interventions to treat alcohol problems [17]. In recent years, the South African National Department of Health and several national organizations have called for increased training of frontline treatment providers in screening and brief alcohol intervention as a means of mitigating the effects of alcohol on the HIV care continuum [18].…”
Section: Introductionmentioning
confidence: 99%